Problem-Solving Pedagogy and Attitudinal Change in Mathematics: A Quasi-Experimental Study in Nigerian Secondary Schools - Danlami, Kazaik Benjamin; Ayuba, Istafanus; Anas, Halliru; Ezumezuh, Gladys (LPPM Universitas Terbuka, 2025)
This study examined the effect of a Pólya-based problem-solving instructional strategy on senior secondary students’ attitudes toward mathematics in Kaduna State, Nigeria. Guided by constructivist learning theory, the study adopted a quasi-experimental pretest–posttest control group design involving 200 students purposively selected from public schools. The Mathematics Attitude Questionnaire (MAQ) was administered before and after a six-week intervention to measure enjoyment, anxiety, perceived competence, and perceived usefulness. The experimental group received instruction based on Pólya’s four-step model, while the control group received conventional teaching. Data was analyzed using descriptive statistics and analysis of covariance (ANCOVA) to control baseline attitudes. Results revealed that although the problem-solving group achieved higher mean post-test attitude scores, the difference was not statistically significant (p > .05). Pre-attitude scores were the strongest predictor of post-attitudes, indicating that existing dispositions largely determined outcomes. These findings suggest that short-term problem-solving interventions may foster slight positive trends but require longer and more sustained implementation to produce significant attitudinal change. The study recommends integrating structured problem-solving with effective support strategies to enhance students’ confidence and interest in mathematics.